Rubus crataegifolius Bunge regulates adipogenesis through Akt and inhibits high-fat diet-induced obesity in rats. Issue 1 (December 2016) - Jung, Min-Sup; Lee, Soo-Jung; Song, Yuno; Jang, Sun-Hee; Min, Wongi; Won, Chung-Kil; Kim, Hong-Duck; Kim, Tae; Cho, Jae-Hyeon
Abstract Background Obesity is one of the greatest public health problems and major risk factors for serious metabolic diseases and significantly increases the risk of premature death. The aim of this study was to determine the inhibitory effects of Rubus crataegifolius Bunge (RCB) on adipocyte differentiation in 3 T3-L1 cells and its anti-obesity properties in high fat diet (HFD)-induced obese rats. Methods 3 T3-L1 adipocytes and HFD-induced obese rats were treated with RCB, and its effect on gene expression was analyzed using RT-PCR and Western blotting experiments. Results RCB treatment significantly inhibited adipocyte differentiation by suppressing the expression of C/EBPβ, C/EBPα, and PPARγ in the 3 T3-L1 adipocytes. Subsequently, the expression of the PPARγ target genes aP2 and fatty acid synthase (FAS) decreased following RCB treatment during adipocyte differentiation. In uncovering the specific mechanism that mediates the effects of RCB, we demonstrated that the insulin-stimulated phosphorylation of Akt strongly decreased and that its downstream substrate phospho-GSK3β was downregulated following RCB treatment in the 3 T3-L1 adipocytes. Moreover, LY294002, an inhibitor of Akt phosphorylation, exerted stronger inhibitory effects on RCB-mediated suppression of adipocyte differentiation, leading to the inhibition of adipocyte differentiation through the downregulation of Akt signaling. An HFD-induced obesity rat model was used to determine the inhibitory effects of RCB on obesity. Body weight gain and fat accumulation in adipose tissue were significantly reduced by the supplementation of RCB. Moreover, RCB treatment caused a significant decrease in adipocyte size, associated with a decrease in epididymal fat weight. The serum total cholesterol (TC) and triglyceride (TG) levels decreased in response to RCB treatment, whereas HDL cholesterol (HDL-C) increased, indicating that RCB attenuated lipid accumulation in adipose tissue in HFD-induced obese rats. Conclusion Our results demonstrate an inhibitory effect of RCB on adipogenesis through the reduction of the adipogenic factors PPARγ, C/EBPα, and phospho-Akt. RCB had a potent anti-obesity effect, reducing body weight gain in HFD-induced obese rats.